Practice makes perfect: a review of banking in Central and Eastern Europe - Armin Riess; Rien Wagenvoort; Peter Zajc (EIB Papers, 2002)
Planned economies produced many goods and services - such as cars, electricity, and machinery - that did not differ fundamentally from those available in market economies. Certainly, the quality and variety of these goods and services did not reach Western standards and there was an almost perennial mismatch between demand and supply, with an excess demand for many goods and an over-supply of others. Yet, there was a supply of cars, electricity, machinery, and the like. This cannot be said about banking services, or finance in general, as known in market economies. For sure, there were financial flows and payments. But to the extent that they accompanied investment, they largely followed real resources that had been allocated before under the central plan, which - in turn - saw no need for key banking functions such as transforming assets, managing risks, and processing information on and monitoring of borrowers. In creating market-driven banking sectors, all Central and Eastern European accession countries (CEECs) (1) encountered similar problems, notably a substantial amount of bad loans inherited from the communist past and the accumulation of new non-performing loans in the early years of transition. The latter was due to a combination of factors, in particular an inevitable lack of expertise in commercial banking, continued lending of incumbent banks to enterprises from the communist past with a doubtful future in an open economy, imprudent or fraudulent lending by a rapidly growing number of new banks, and - last but not least - weak banking sector regulation and supervision.
Keywords: 330; Bank; Übergangswirtschaft; Bankenreform; Osteuropa